1995
DOI: 10.1074/jbc.270.32.18983
|View full text |Cite
|
Sign up to set email alerts
|

C-type Natriuretic Peptide Increases Bone Resorption in 1,25-Dihydroxyvitamin D3-stimulated Mouse Bone Marrow Cultures

Abstract: Most agents that regulate osteoclast bone resorption exert their effects indirectly, through the osteoblast. Nitric oxide, which stimulates soluble guanylyl cyclase, has been reported to inhibit osteoclast bone resorption directly, by a cGMP-independent mechanism (1). In this report, we demonstrate that C-type natriuretic peptide (CNP), an activator of membrane-bound guanylyl cyclase, stimulates bone resorption by osteoclast-containing 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3)-stimulated mouse bone marrow cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
68
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 39 publications
1
68
0
3
Order By: Relevance
“…Immunoprecipitation and Immunoblots-Osteoclasts were generated from primary mouse marrow cultures as previously described (24). RAW 264 cells were cultured in RPMI medium (Life Technologies, Inc.) containing 10% fetal calf serum (Life Technologies) and osteoprotegerin ligand (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation and Immunoblots-Osteoclasts were generated from primary mouse marrow cultures as previously described (24). RAW 264 cells were cultured in RPMI medium (Life Technologies, Inc.) containing 10% fetal calf serum (Life Technologies) and osteoprotegerin ligand (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse Marrow Cultures-Osteoclasts were generated from primary mouse marrow cultures (12). 8 -20 g Swiss-Webster mice were killed by * This work was supported by an Arthritis Investigator Award from the Arthritis Foundation (to L. S. H.) and National Institutes of Health Grants RO1 DK52131 (to B. S. L.), RO1 DK38848 (to S. L. G.), and PO1 AR32087.…”
Section: Methodsmentioning
confidence: 99%
“…Bone Resorption Assays-Assays were performed essentially as described previously (12) with slight modifications to allow immunoprecipitations to be performed from bone resorptive cells. Mouse marrow cultures were grown to maturity in tissue culture plates, then scraped and loaded onto 8-cm 2 dentine slices in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using primary cultures of osteoblast-like cells and chondrocytes, and osteoclast-containing bone marrow cultures, or cultured cell lines such as osteoblastic MC3T3-E1 cells have suggested that natriuretic peptides modulate the proliferation and differentiation of osteoblasts, chondrocytes, and osteoclasts in vitro (15)(16)(17)(18). However, whether natriuretic peptides can regulate bone formation in vivo has remained to be elucidated.…”
mentioning
confidence: 99%